2019
DOI: 10.1080/20013078.2019.1690217
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles containing oncogenic mutant β‐catenin activate Wnt signalling pathway in the recipient cells

Abstract: Mutations in β-catenin, especially at the residues critical for its degradation, render it constitutively active. Here, we show that mutant β-catenin can be transported via extracellular vesicles (EVs) and activate Wnt signalling pathway in the recipient cells. An integrative proteogenomic analysis identified the presence of mutated β-catenin in EVs secreted by colorectal cancer (CRC) cells. Follow-up experiments established that EVs released from LIM1215 CRC cells stimulated Wnt signalling pathway in the reci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 38 publications
2
47
0
Order By: Relevance
“…Whilst some of the uptake mechanisms have been proven with cell biology-based experiments, there is limited evidence for other pathways. For instance, receptor-mediated endocytosis seems to be the most preferred uptake route of EVs, as suggested by several studies [ 157 , 158 , 159 , 160 ] Regardless, the first step in this process is binding between EVs and their target cells, through specific interactions between proteins such as tetraspanins, integrins, cytokines and lipids enriched at the surfaces of the EVs and receptors such as intercellular adhesion molecules embedded on the plasma membranes of the target cells [ 12 , 161 ]. This has been shown to occur for a number of cell types including liver, lung, lymph node, neural and dendritic and intestinal epithelial cells [ 162 , 163 , 164 ].…”
Section: Extracellular Vesicles (Evs)mentioning
confidence: 85%
“…Whilst some of the uptake mechanisms have been proven with cell biology-based experiments, there is limited evidence for other pathways. For instance, receptor-mediated endocytosis seems to be the most preferred uptake route of EVs, as suggested by several studies [ 157 , 158 , 159 , 160 ] Regardless, the first step in this process is binding between EVs and their target cells, through specific interactions between proteins such as tetraspanins, integrins, cytokines and lipids enriched at the surfaces of the EVs and receptors such as intercellular adhesion molecules embedded on the plasma membranes of the target cells [ 12 , 161 ]. This has been shown to occur for a number of cell types including liver, lung, lymph node, neural and dendritic and intestinal epithelial cells [ 162 , 163 , 164 ].…”
Section: Extracellular Vesicles (Evs)mentioning
confidence: 85%
“…130 The CRC cells secreted exosomes could transfer mutated β-catenin to recipient cells activating Wnt signaling and enhance tumor burden in xenograft mice models. 131 TGF-β and WNT/β-catenin signaling pathways are key regulators in EMT. [132][133][134] Exosomes derived from HCC cells could mediate EMT through activating TGF-β/Smad signaling pathway, inducing a decrease in E-cadherin expression, but an increase in Vimentin, which resulted in promoted migration and invasion of target cells.…”
Section: Exosome and Cancer-associated Fibroblastsmentioning
confidence: 99%
“…Kalra et al [ 129 ] have shown that EVs released by CRC cells and containing the mutant β-catenin and high Wnt/β-catenin activity boost the expression of target genes as c-myc and cyclin D1 when transferred to recipient cells ( Table 3 ).…”
Section: Extracellular Vesicles and The Wnt Pathwaymentioning
confidence: 99%